The relationship between irrational beliefs and adjustment of female high school students - Chia, Chui Ting, 1989- author; Ahmad Shukri Mohd. Nain, supervisor; Fakulti Pengurusan (2014)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2014